(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: The boom of other parallel industries of the hotel industry has given a great competition of human resource as the source is same that is Hotel Management graduates. The situation has led to fear of a decline in the qualified future hoteliers in hotels.Objective: To study the factors that are influencing the students opting out of hotels and looking forward to start a career in other allied industries. Methodology: In this study, quantitative research method was used and research data were collected by questionnaire technique. The sample comprised of 60 students of batch 2015 and 2016 of IHM PUSA, New Delhi. The attitude was assessed using likert scale questionnaire. Results: The subject has very high preference for starting their career in industries other than hotels. It was also observed that around 35% subject wants to join Hotels or Retail sector. Conclusion: Many of hotel management graduates are not joining hotels due to various factors from Industrial Training to remunerations.